Dengue IgG Seropositivity and Zika Viral Load. (4th October 2017) - Read, Jennifer; Alvarado, Luisa I; Torres-Velasquez, Brenda; Munoz-Jordan, Jorge L; Beltran, Manuela; Capre, Sheila; Adams, Laura; Torres-Torres, Sanet; Santiago, Gilberto; Rivera, Lillian; Rivera-Sánchez, Aidsa; Lorenzi, Olga D; et al.
Abstract: Background: Secondary dengue virus (DENV) infections are typically more severe than primary infections. It is not known whether previous DENV infection is associated with higher Zika virus (ZIKV) quantitative RT-PCR results (viral loads (VLs)) in areas endemic for DENV such as Puerto Rico. Our objective was to analyze the association between previous DENV infection (DENV IgG-positive) and ZIKV VL among children with symptomatic ZIKV infection enrolled in the Sentinel Enhanced Dengue and Acute Febrile Illness Surveillance System (SEDSS) in Puerto Rico. Methods: The study population for this analysis comprised individuals <18 years of age enrolled in SEDSS during 2016 who were ZIKV PCR-positive in serum (using the CDC Trioplex RT-polymerase chain reaction (RT-PCR) assay) within 5 days post-onset (DPO) of symptoms. ZIKV VLs (genome copies/mL) were determined using an RNA standard curve generated from the RT-PCR assay target amplicons. An in-house ELISA was used to ascertain the presence or absence of serum DENV IgG. Trends were assessed using Jonckheere-Terpstra and Chi-square for proportions tests. The Mann–Whitney-Wilcoxon test was used to compare medians. Linear regression modeling was used to determine the association between DENV IgG and ZIKV VL. Results: Of the 319 individuals who met inclusion criteria, 163 have dengue IgG assays completed to date. Of these, 90/163 (55%) were DENV IgG-positive and 73/163 (45%) were DENV IgG-negative, and did not vary by sex ( P = 1.00). However, the proportion of patients with DENV IgG-positivity increased with age (P < 0.001) (Figure). Overall, the median (interquartile range, IQR) ZIKV VL was 23, 110 (7, 452–84, 003), and did not vary by age ( P = 0.11) or sex ( P = 0.33). However, the median ZIKV VL varied by DPO: 26, 230 (DPO<3; n = 117), 15, 159 (DPO≥ 3; n = 46), P = 0.002. The median (IQR) ZIKV VLs were: 24, 073 (10, 938–73, 130) in DENV IgG-negative specimens and 22, 658 (7, 332–89, 322) in DENV IgG-positive specimens ( P = 0.91). Linear regression indicated no association between DENV IgG and ZIKV VL ( P = 0.54). Conclusion: DENV IgG-positivity increased with age among children with symptomatic ZIKV infection. ZIKV VLs did not vary by age, but decreased with increasing DPO. There was no association between DENV IgG and ZIKV VL. Disclosures: All authors: No reported disclosures.